Comparing the effects of cold therapy and hand and foot massage on postoperative pain among patients with major surgeries - Ali Miri; Reza Masoudi; Soleiman Kheiri; Shirmohammad Davoodvand (Shahrekord University of Medical Sciences, 2021)
Background and aims: Surgery is a main treatment for some illnesses. Postoperative pain (POP) is a major postoperative concern for patients and healthcare providers. The present study aimed at comparing the effects of cold therapy and foot and hand massage on POP among patients with major surgeries. Methods: This quality improvement study was conducted in 2019 on ninety patients who underwent thoracoabdominal surgeries in Kashani teaching hospital, Shahrekord, Iran. Participants were randomly assigned to a control, a cold therapy, and a foot and hand massage group through block randomization with a block size of six. Participants in the control group received routine care services, while participants in the cold therapy group received twenty-minute local cold therapy three times a day for 48 hours and participants in the massage group received twenty-minute hand and foot massage three times a day for 48 hours. POP was assessed before and 48 hours after the study intervention using the McGill Pain Questionnaire. The SPSS software was used to analyze the data through the Kolmogorov-Smirnov, Fisher's exact, chi-square, Kruskal-Wallis, paired-sample t, and Wilcoxon's sign-ranked tests as well as the one-way analysis of variance. Results: There was no significant difference among the groups respecting the pretest mean score of POP (P > 0.05). The mean score of POP significantly decreased in all groups (P < 0.05) and the amount of decrease in the intervention groups was significantly more than the control group (P < 0.05). Conclusion: Cold therapy and foot and hand massage are effective in significantly reducing POP among patients with major thoracoabdominal surgeries.